Microwave ablation: an effective treatment for mild-to-moderate secondary hyperparathyroidism in patients undergoing haemodialysis - Wang, Gang; Liu, Sha; Liu, Xu; Qian, Linxue; Diao, Zongli; Liu, Wenhu (International journal of hyperthermia, 2017)
Background: Microwave ablation (MWA) is an effective treatment for severe secondary hyperparathyroidism (SHPT), but it can also be used for mild-to-moderate secondary hyperparathyroidism (SHPT). In this randomised, controlled study, the efficacy of MWA in the treatment of mild-to-moderate hyperparathyroidism is investigated. Materials and methods: We assessed outcomes 12 months after the randomisation of 28 patients with mild-to-moderate SHPT. The subjects received either MWA plus calcitriol or calcitriol alone. The primary end-points were the rate of achieving target levels of intact parathyroid hormone (iPTH), changes in iPTH levels and the rate of patients developing severe SHPT. Results: Primary end points: the overall rates of achieving target levels of iPTH were comparable between the MWA and calcitriol alone groups (24% vs. 22%, p = 0.85). However, the rate of iPTH <150 pg/mL (lower limit of the target range) in the MWA group was higher than that in the calcitriol alone group (23% vs. 8%, p = 0.02). The mean iPTH level in the MWA group after MWA was lower than that in the calcitriol alone group (373.09 ± 322.31 vs. 552.28 ± 361.87 pg/mL, p < 0.001). There was a significant difference in the change in iPTH levels over time within the MWA group (p < 0.001) but not in the calcitriol alone group. Only one patient developed severe SHPT in the MWA group, while six patients in the calcitriol alone group developed severe SHPT (p = 0.04). Conclusions: Compared with calcitriol alone, MWA plus calcitriol decreases iPTH levels and prevents the progression of mild-to-moderate SHPT.